Body image and nutritional status of academics from nutrition course in private University of Alfenas - Silva, Giuliano Roberto da; Siqueira Vilela Terra, Gerusa Dias; Tavares, Marcelo Rodrigo; Neiva, Cassiano Merussi [UNESP]; Bueno, Julia Macedo; Marinho, Camila Ferreira; Forsan, Camila Nogueira; Paiva, Marcela Adell (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2016)
Introduction: Body image is the image that has mentally about the size and shape of the body, including feelings related to these characteristics and body parts. However, the distortion and dissatisfaction with body image, cause eating disorders (bulimia, anorexia nervosa, morbid obesity), recent being in the literature observation of such distortion in normal weight subjects. Aim: To evaluate body image and nutritional status of academics from Nutrition Course in order to identify possible distortions and dissatisfaction in body perception. Materials and Methods: We measured weight and height with which we calculated the body mass index (BMI Real), n = 44 students, 18-45 years of the Nutrition course. The assessment of body image was performed by Figures Scale Silhouettes, where each participant chose a figure for the image that has of his own body (current BMI) and a picture with the silhouette you would like to have (desired BMI). Results: It was found that there was a prevalence of normality in relation to nutritional status among the study participants. Regarding the perception and satisfaction of body image, it was observed that had a distorted (p = 0.06) and body image dissatisfaction (p = 0.058). Conclusion: The results indicate that other aspects of body image perception are studied as important subjective components in adopting attitudes and practices determinants of eating behavior and nutritional status.
Keywords: Students; Self-image; Feeding Behavior; Distorted Body Image